2015
DOI: 10.1021/acs.biochem.5b00263
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of GeoCyp: A Thermophilic Cyclophilin with a Novel Substrate Binding Mechanism That Functions Efficiently at Low Temperatures

Abstract: Thermophilic proteins have found extensive use in research and industrial applications because of their high stability and functionality at elevated temperatures while simultaneously providing valuable insight into our understanding of protein folding, stability, dynamics, and function. Cyclophilins, constituting a ubiquitously expressed family of peptidyl–prolyl isomerases with a range of biological functions and disease associations, have been utilized both for conferring stress tolerances and in exploring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 78 publications
4
50
0
Order By: Relevance
“…33 We have previously demonstrated that CypA and GeoCyp both bind to and catalyze isomerization of this peptide. 24 Here, we have also characterized the activities of two additional human cyclophilins, CypB and CypC, toward this substrate. The chemical shifts of CypA, 25 CypB, 27 and GeoCyp 26 have been previously published, but not those for CypC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 We have previously demonstrated that CypA and GeoCyp both bind to and catalyze isomerization of this peptide. 24 Here, we have also characterized the activities of two additional human cyclophilins, CypB and CypC, toward this substrate. The chemical shifts of CypA, 25 CypB, 27 and GeoCyp 26 have been previously published, but not those for CypC.…”
Section: Resultsmentioning
confidence: 99%
“…24 Multiple residues exhibit distinct cis and trans amide chemical shifts, including two resides (Asp 6 and Leu 7) for which the cis, trans , and cross-peaks are resolvable (one cross-peak for Asp 6 is overlapped with another residue peak). The time-dependent disappearance of the cis and trans peaks and appearance of cross-peaks can be used to determine an isomerization rate ( k iso ) between the two free isoforms under the given conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NMR chemical shifts were determined as previously described (41). The catalytic isomerization rates were determined by ZZ exchange as previously described (41).…”
Section: Methodsmentioning
confidence: 99%
“…The NMR chemical shifts were determined as previously described (41). The catalytic isomerization rates were determined by ZZ exchange as previously described (41). More specifically, ZZ-exchange data were collected on 1 mM 15 N-labeled peptide with 20 μM unlabeled wild-type CypA or V29L CypA mutant at 10°C on a Varian 600 MHz spectrometer with a cryogenically cooled probe.…”
Section: Methodsmentioning
confidence: 99%